MINAT DAN PILIHAN POLITIK ORANG KRISTEN INDONESIA 1955 - 2009 Sebuah Kajian Historis-teologis - Jan S. Aritonang (Studia Philosophica et Theologica, 2009)
The presence of Christianity in Indonesia was connected very much with political interest and goal by some European nations. But not until the end of the 19th century the indigenous Christians involved in political life and showed their interest in political matters. From the beginning of the 20th century some Christian political parties emerged gradually and one of the strongest was Parkindo (Indonesian Christian Party). This article aims to show the political interest, inclination and option of the Indonesian Christians, esp. during the general election, from 1955 up to 2009, through a historical as well as theological perspective.